Avaliação do ensino-aprendizagem nas licenciaturas em Física do IFCE: conhecendo as práticas e propondo caminhos formativos - Parente, Nórlia Nabuco (2020)
The aim of this study was to investigate the evaluation of learning in Physics undergraduate courses at the Federal Institute of Education, Science and Technology of Ceará (IFCE), and it culminated in pedagogical guidance actions. The analysis and theoretical foundation were based on the generations of evaluation and on the concept of formative evaluation. This study consists of an action research with qualitative methodology, which starts from the following steps: survey of the academic flow rates; analysis of the teachers' and students' perceptions; execution of educational guidance actions; and analysis of the effects . The research subjects are physics and mathematics teachers as well as regularly enrolled students. The actions took place on the campuses of Sobral, Acaraú, Cedro, Tianguá, Crateús and Fortaleza, covering a sample of 246 subjects in a universe of 906. Semi-structured interviews and questionnaires that passed through Content Analysis were used. The pedagogical guidance actions were developed considering the difficulties mentioned in order to discuss the reality of each campus and improve the evaluation. It was concluded that the conception of evaluation of the teachers who participated in the research is linked to the idea of measurement and exam, that the institutional guidelines are partially complied with, and that the teachers had doubts about the diagnostic and qualitative evaluation. In the students' perception, the tests are prioritized, the dialogue about evaluation is informative, and the results are used for classification. It was also concluded that the traditional model influences students who believe that the test is the fairest evaluation form. Failures are frequent in subjects related to mathematics, and they are caused by factors such as time, comprehension of the content, and lack of motivation. The pedagogical orientation actions had positive effects and fostered changes in the practices of the teachers who participated in the research, leading them to consider that it is possible to use training methods. The interventions were evaluated as relevant because they provoked reflection and complemented the training, and they can be recommended to more teachers from IFCE.